Feminist Transformation: Result of the Waves of Feminist Movement - Bhandari, Laxmi Prasad (AMC Journal, 2023)
This article is about feminist transformation. The main objective is to draw the connection of feminist transformation to waves and types of feminism. Document analysis has conducted under qualitative research design for drawing conclusion. The main intention of feminist transformation is to eradicate various forms of oppression and injustice that exist on the basis of gender difference. The right to vote and property ownership, legal and social rights and the use of social media for ending oppression were the achievement of the waves and these achievements were for feminist transformation. On the other hand, all feminism types have the same motive to end oppression on the basis of gender which makes feminist transformation easier. It is concluded that there is the means-end relationship between waves and types of feminism to feminist transformation. The saying and doing of people and authority must be same for true feminist transformation.